PENGARUH TERPAAN DRAMA KOREA PENTHOUSE: WAR IN LIFE TERHADAP PERILAKU IMITASI (SURVEI IBU-IBU PERUMAHAN BUMI CIPTA LARAS 2 DESA CIBALONGSARI KOSAMBI KARAWANG TIMUR) - Islami Yuniartiningsih, (2022)
Over time, Korean dramas are liked by many groups, not only among teenagers, but Korean dramas are also liked by mothers and can have an impact on what happens. The purpose of this study was to determine the influence of exposure to the Korean drama Penthouse: War In Life on imitation behavior (a survey of women in Bumi Cipta Laras 2 Housing, Cibalongsari Kosambi Karawang Timur). The theory in this study uses social learning theory or social learning theory. This research uses quantitative methods and explanatory research types. The population and sample in this study were the women of Bumi Cipta Laras 2 Housing Village, Cibalongsari Kosambi, Karawang Timur. The results of this study state that the magnitude of the influence of exposure to the Korean drama Penthouse: War In Life on imitation behavior that occurs in mothers in Bumi Cipta Laras 2 Housing Village, Cibalongsari Kosambi Karawang Timur is 75.1%, the remaining 24.9% is influenced by environmental factors. Imitation behavior that occurs imitates property (household equipment), imitates clothing styles, imitates Korean, and imitates the love sign pose. Even though it's not quite the same as in the Korean drama Penthouse: War In Life, the mothers choose an alternative path by following the same colors as they see.